"O evangelho segundo Jesus a rainha do céu":: O expurgo social da mulher travesti através de uma decisão judicial - Ferreira, Glenda; Colares, Virgínia (Language and Law / Linguagem e Direito, 2022)
This article examines a court decision issued by judge Roberto da Silva Maia of the Pernambuco Court of Justice (TJPE). It applies Norman Fairclough's Critical Discourse Analysis (CDA), the modes of operation of ideology of John B. Thompson and the Appraisal system developed by Jim Martin & Peter White. We will apply these tools in a form adapted to Brazilian Portuguese by Orlando Vian Jr. Our aim is to identify if there is, in the decision, an attempt to socially purge the transvestite woman. After the analysis, we reflect on the social context in which freedom of artistic expression has caused discomfort and how the arguments used to limit it reinforce the exclusion of and prejudice against transvestite women.